The World of Work in the Context of the COVID-19 Pandemic: Analysis, Assessments and ILO Recommendations - G. L. Podvoisky (Мир новой экономики, 2021)
The crisis caused by the COVID-19 pandemic, unprecedented in scale, speed, and depth, has imbalanced and destabilized national labour markets. This article highlights the work of the International Labour Organization (ILO), which since the start of the pandemic has made a signifiant contribution to analysing the situation in the crisis and developing practical recommendations for the restoration of labour markets. The author of the article examines the key challenges facing national governments in this challenging and responsible period, including those identifid by ILO Director-General Guy Ryder. Particular attention is paid to the analysis of the consequences of introducing strict restrictive measures, primarily the closure of jobs. Data on lost working time in various regions and subregions of the world are provided. Based on international labour standards, ILO experts have formulated the main directions for combating the crisis caused by COVID-19, the implementation of which will contribute to faster recovery and stabilisation in national labour markets.